Reduced leptin level is independent of fat mass changes and hunger scores from high-intensity intermittent plus strength training - Inoue, Daniela S. [UNESP]; Panissa, Valéria L.; Antones, Barbara M. [UNESP]; Oliveira, Flaviane P. [UNESP]; Malta, Raoni B. [UNESP]; Caldeira, Renan S. [UNESP]; Campos, Eduardo Z.; Pimentel, Gustavo D.; Franchini, Emerson; Lira, Fábio S. [UNESP] (Edizioni Minerva Medica, 2018)
BACKGROUND: This study aimed to analyze the effects of high-intensity intermittent training (HIIT) plus strength training on body composition, hormone related to energy balance (leptin), and hunger scores in physically active non-obese men. METHODS: Sixteen men were allocated in two different groups, training group (N.=10) performed a combined HIIT (5 km, 1 minute of effort interspersed by 1 minute of rest in passive recovery) followed by strength exercise session (three sets, with load of 8-12 repetition maximum) twice a week, during 8 weeks, while control group (N.=6) did not suffer any intervention. Hunger scores, leptin concentrations and body composition were assessed. Body composition, fasting leptin and hunger score were compared through two-way analysis (group and period) with repeated measures in the second factor while leptin and hunger scores in exercise session pre- and post-8 weeks through two-way analysis (period and time of measurement) with repeated measures in the second factor. RESULTS: The fasting leptin decreased pre- to post-8week in training group (7.7±4.9 to 2.9±2.1 ng/mL; P=0.012). For leptin response to exercise session there was main effect of training period, with higher values pre- (6.5±3.9 ng/mL) than post-training (2.6±2.1 ng/mL; P<0.001). For hunger scores there was effect of time of measurement (P<0.001), decreasing after breakfast and increasing over the experiment. CONCLUSIONS: Combined HIIT plus strength training were able to promote alterations in a hormone related to energy balance independent of body composition and hunger index alterations in physically active non-obese men.
Keywords: Body composition; Energy metabolism; Exercise; High-intensity interval training; Leptin